2020
DOI: 10.1038/s41598-020-73661-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the natural alkaloid Berberine affects cardiovascular system morphogenesis and functionality during zebrafish development

Abstract: The plant-derived natural alkaloid berberine displays therapeutic potential to treat several pathological conditions, including dyslipidemias, diabetes and cardiovascular disorders. However, data on berberine effects during embryonic development are scarce and in part controversial. In this study, using zebrafish embryos as vertebrate experimental model, we address the effects of berberine treatment on cardiovascular system development and functionality. Starting from the observation that berberine induces dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
(163 reference statements)
1
9
0
Order By: Relevance
“…Berberine is a multifunctional, natural product with therapeutic potential in vascular diseases, including cardiovascular disease, atherosclerosis, hypertension, cerebrovascular disease, diabetes and associated complications, intestinal vascular disease and cancer ( Zhu et al, 2018 ; Martini et al, 2020 ; Yin et al, 2021 ). The present review has shown the excellent protective effect of berberine in diverse vascular diseases by preserving vascular endothelial cells, improving vascular remodeling and vasoconstriction, and suppressing inflammation, oxidative stress, autophagy, and apoptosis, based on recent in vitro and in vivo experimental reports ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Berberine is a multifunctional, natural product with therapeutic potential in vascular diseases, including cardiovascular disease, atherosclerosis, hypertension, cerebrovascular disease, diabetes and associated complications, intestinal vascular disease and cancer ( Zhu et al, 2018 ; Martini et al, 2020 ; Yin et al, 2021 ). The present review has shown the excellent protective effect of berberine in diverse vascular diseases by preserving vascular endothelial cells, improving vascular remodeling and vasoconstriction, and suppressing inflammation, oxidative stress, autophagy, and apoptosis, based on recent in vitro and in vivo experimental reports ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Berberine is a multifunctional, natural product with therapeutic potential in vascular diseases, including cardiovascular disease, atherosclerosis, hypertension, cerebrovascular disease, diabetes and associated complications, intestinal vascular disease and cancer (Zhu et al, 2018;Martini et al, 2020;Yin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed that BBR is cardiotoxic, leading to total amplitude and beating rate inhibition at 10 μM in cardiomyocytes ( Zhang et al, 2018 ). Animal experiments have suggested that BBR exerts toxic and teratogenic effects in developing zebrafish embryos at 400 mg/L for a-48 h administration, as evidenced by pericardial edema, damaged heart morphogenesis, vascular defects, and death ( Martini et al, 2020 ). BBR treatment during vertebrate development leads to the impairment of cardiovascular system morphogenesis and functionality, suggesting it should be used with caution during pregnancy and lactation.…”
Section: The Admet Properties Of Bbrmentioning
confidence: 99%